Genus-Zuweisung bei der Pronominalisierung von Personen in den Südwalser Dialekten - Zürrer, Peter (Linguistik Online, 2021)
The Alemannic dialects in linguistic islands in Northern Italy have been undergoing strong changes since the second half of the 20th century. One of these changes concerns the assignment of gender with persons. Generalized neuter abolishes the coupling of gender with male/female and transfers both female and male persons into neuter. This in turn has its effect on verbal inflection. The post-verbal subject clitics mutate in the 3rd person singular to verb endings void of male/female connotations. This change, as it is now spreading, is not in itself a recent phenomenon. In early written dialectal records it already occurs in single documents even at the beginning of the 19th century.